Bopys don't cry. Masculinities, fear of crime and fearlessness - Goodey, Jo (The British journal of criminology, 1997)
The gendered stereotypes of fearless male/fearful female' are not supported by the reality of complex and multiple identities and the shifting meanings of fear and fearlessness which are brought to and evolve from these identities. Referring to evidence from the author's own research, childhood and adolescence are put forward as crucial stages in identity development where one can begin to unpack the processes by which gendered meanings of fear and fearlessness become fixed'. This paper argues that the image of the fearless' male, from childhood onwards, is not a helpful one. The benefits to the male sex from taking on a fearless' persona, alongside its negative social implications, are discussed with reference to hegemonic masculinity. Class and race are put forward as significant variables in the development of hegemonic masculinity's emotionally inarticulate persona and racism is highlighted as one of the ugliest expressions of exaggerated masculinity. The above is placed and developed within the theoretical context of the hegemonic masculine biography'